1985
DOI: 10.1099/0022-1317-66-5-1139
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Caprine Arthritis-Encephalitis Retrovirus Proteins in Immunodiffusion Precipitin Lines

Abstract: SUMMARYPrecipitin lines formed between serum from a goat infected with caprine arthritis encephalitis virus (CAEV) and radiolabelled viral proteins in polyethylene glycolconcentrated culture medium were excised from immunodiffusion (ID) plates and analysed by polyacrylamide gel electrophoresis. The two major precipitin lines contained the 135 000 mol. wt. glycoprotein (gp135) and the internal 28000 mol. wt. structural protein (p28). This method obviates the use of purified proteins or monospecific antisera to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1985
1985
1993
1993

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In this regard, group-specific epitopes associated with the major structural protein of the ovine viruses are exhibited by the p28 of all CAEV isolates so far examined. Antigenic 0000-6476 © 1985 SGM cross-reactivity between the 135K surface glycoproteins of caprine and ovine viruses has also been observed (Dahlberg et al, 1981;Pyper et al 1984;Adams et al, 1985b) although neutralizing antisera appear to be specific for individual virus isolates . Dahlberg et al (1981) reported that PPV core proteins other than p28 are not immunoreactive with goat anti-CAEV serum.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, group-specific epitopes associated with the major structural protein of the ovine viruses are exhibited by the p28 of all CAEV isolates so far examined. Antigenic 0000-6476 © 1985 SGM cross-reactivity between the 135K surface glycoproteins of caprine and ovine viruses has also been observed (Dahlberg et al, 1981;Pyper et al 1984;Adams et al, 1985b) although neutralizing antisera appear to be specific for individual virus isolates . Dahlberg et al (1981) reported that PPV core proteins other than p28 are not immunoreactive with goat anti-CAEV serum.…”
Section: Introductionmentioning
confidence: 99%
“…For serology, the immunodiffusion test and ELISA are most commonly used [8,11,12,15,20]. It should be noted that virus-positive animals may give a seronegative result shortly before death [unpublished observa tions].…”
Section: Virus Isolation and Serologymentioning
confidence: 99%
“…Various techniques are used for the serologic diagnosis of infection with caprine and ovine lentiviruses. These include agar gel precipitation (1,5,8), indirect enzyme-linked immunosorbent assay (ELISA) (4, 6), and ELISA based on a double-antibody sandwich blocking procedure (7). The main problems with all assays are validation and standardization.…”
mentioning
confidence: 99%